2016
DOI: 10.4073/csr.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Business Support Services for Small and Medium Enterprises on Firm Performance in Low‐ and Middle‐Income Countries: A Systematic Review

Abstract: This Campbell systematic review assesses the effects of business support services in low‐ and middle‐income countries on firm performance and economic development. The review summarizes findings from 40 studies. Included studies examine interventions targeted at SMEs (two to 250 employees) involving tax simplification, exports and access to external markets; support for innovation policies; support to local production systems; training and technical assistance, and SME financing and credit guarantee programmes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 57 publications
1
43
1
Order By: Relevance
“…In addition to evaluations based on experimental and quasi-experimental designs, the study also includes tracer studies as well as monitoring and evaluation reports that rely largely on administrative data. The study does not include a statistical meta-analysis or study effect sizes Piza et al (2016). review the impacts of business support services for small and medium-sized enterprises (SMEs) on firm performance indicators, employment generation and labour productivity in low-and middle-income countries.…”
mentioning
confidence: 99%
“…In addition to evaluations based on experimental and quasi-experimental designs, the study also includes tracer studies as well as monitoring and evaluation reports that rely largely on administrative data. The study does not include a statistical meta-analysis or study effect sizes Piza et al (2016). review the impacts of business support services for small and medium-sized enterprises (SMEs) on firm performance indicators, employment generation and labour productivity in low-and middle-income countries.…”
mentioning
confidence: 99%
“…Intercept [13], [4], [7], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27] Relative Advantage Compatibility IT Infrastructure Security Organizational Factors Involvement & Consistency [12], [28], [10], [29], [30], [31] Top Management Support Financial Resources Human Resources…”
Section: Factors Critical References Technology Factorsmentioning
confidence: 99%
“…Okpara (2011) suggested that a positive relationship exists between small business development and economic growth. Small-scale enterprises also remain critically important for the advancement of any nation's economy (Piza et al, 2016;Tomaselli et al, 2013). SMEs also are regarded as an excellent source of development that help in the improvement of local technology and the development of indigenous entrepreneurs.…”
Section: Literature Review and Conceptual Designmentioning
confidence: 99%